2015
DOI: 10.18632/oncotarget.4249
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 activity as a potential biomarker for the pan-epigenetic anticancer agent, RRx-001

Abstract: Nuclear factor erythroid 2-related factor 2 (Nrf2) is a master regulatory transcription factor that plays an important role in the antioxidant response pathway against anticancer drug-induced cytotoxic effects. RRx-001 is a new anticancer agent that generates reactive oxygen and nitrogen species, and leads to epigenetic alterations in cancer cells. Here we report the RRx-001 mediated nuclear translocation of Nrf2 and the activation of expression of its downstream enzymes HO-1 and NQO1 in tumor cells. Inhibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 30 publications
2
25
0
Order By: Relevance
“…Our finding in MM cells is consistent with similar observations using RRx-001 in other cell systems 53, 54 .…”
Section: Discussionsupporting
confidence: 93%
“…Our finding in MM cells is consistent with similar observations using RRx-001 in other cell systems 53, 54 .…”
Section: Discussionsupporting
confidence: 93%
“…We observed elevated levels of this protein in cells subjected to hypoxia combined with GYY4137. These results are in agreement with results obtained in study of Zhang and coworkers, who found that in human breast cancer the high NR2F2 transcript level was associated with favorable clinical outcome, which might be due to NR2F2 0 s inhibitory effect on TGF-b-dependent EMT and its role in inhibiting chemoresistance [35]. However, controversial data obtained by other experiments (for example, NR2F2 expression) was found both a positive (ovarian) and negative (prostate and breast) prognostic factor for cancer patients [36].…”
Section: Discussionsupporting
confidence: 93%
“…Multiple lines of evidence indicate that metabolites of RRx-001 cross the blood-brain barrier: (1) in an ADME study with 14 C-labeled RRx-001, radioactivity was detected in the CNS [8]; (2) in an ongoing Phase I/II trial acronymed BRAINSTORM, a significant reduction in the Dynamic contrast-enhancedmagnetic resonance imaging (DCE-MRI)-derived volume transfer constant, K trans , has been demonstrated in multiple patients after one dose of single agent RRx-001, indicative of reduced vascular permeability; and (3) the combination of RRx-001 with artemisinin, in an experimental cerebral malaria model, synergistically decreased animal mortality, neurocognitive sequelae, cerebral vascular changes, and inflammatory cell accumulation in brain microvessels [10].…”
Section: Chemical Structurementioning
confidence: 99%
“…The protective effects of RRx-001 on normal tissue may be mediated through the induction of the Nrf2-regulated antioxidant cell response, which neutralizes free radical damage [2]. In addition to radioprotective properties, RRx-001 is also associated with chemoprotection.…”
Section: Protection Of Normal Tissue From Radiation Chemotherapy Damagementioning
confidence: 99%
See 1 more Smart Citation